Assessing long term effects of compost fertilization on soil fertility and nitrogen mineralization rate. Issue 2 (6th February 2023) - Reimer, Marie; Kopp, Clara; Hartmann, Tobias; Zimmermann, Heidi; Ruser, Reiner; Schulz, Rudolf; Müller, Torsten; Möller, Kurt
Abstract: Background: Fertilization with organic waste compost can close the nutrient cycles between urban and rural environments. However, its effect on yield and soil fertility must be investigated. Aim: This study investigated the long‐term effect of compost on soil nutrient and potentially toxic elements (PTEs) concentration, nutrient budgets, and nitrogen (N) mineralization and efficiency. Methods: After 21 years of annual compost application (100/400 kg N ha –1 year –1 [100BC/400BC]) alone and combined with mineral fertilization, soil was analyzed for pH, organic carbon (SOC), nutrient (total N and P, Nmin, extractable CAL‐P, CAL‐K, and Mg), and PTE (Cu, Ni, Zn) concentrations. Yields were recorded and nutrient/PTE budgets and apparent net mineralization (ANM, only 2019) were calculated. Results: N efficiency was the highest in maize and for mineral fertilization. Compost application led to lower N efficiencies, but increased ANM, SOC, pH, and soil N, and surpluses of N, P, and all PTEs. Higher PTE concentrations were only found in 400BC for Cu. Nutrient budgets correlated with soil nutrient concentration. A surplus of 16.1 kg P ha –1 year –1 and 19.5 kg K ha –1 year –1 resulted in 1 mg kg –1 increase in CAL‐P and CAL‐K over 21 years. Conclusion: Compost application supplies nutrients to crops with a minor risk of soil‐accumulation of PTEs. However, the nutrient stoichiometry provided by compost does not match crop offtakes causing imbalances. Synchronization of compost N mineralization and plant N demand does not match and limits the yield effect. In winter wheat only 65–70% of N mineralization occurred during the growth period.